ACADEMIC WRITING: PRACTICAL TIPS FOR WRITING SCIENTIFIC WORKS - Beatriz Coelho Soares , Bruna (Revista Gênero e Interdisciplinaridade, 2022)
Writing an academic text can be a very challenging process for undergraduates and graduate students. One of the explanations is the fact that it is a skill that not all people master or have ease. In addition, scientific writing is part of a broader thought-making process and involves revisions and rewrites until the design of the final product. Therefore, this material arises as a result of consulting and advisory experiences for the preparation of academic papers.